A Rare Cause of Scrotal Swelling: Transitional Cell Carcinoma of the Bladder Presenting as a Testicular Metastasis - W. Mahmalji; S. Jain; M. Stower (Advances in Urology)
A 72-year-old Caucasian male who presented with haematuria in July of 2000 was found to have a large left-sided bladder tumour. He underwent a transurethral resection of the tumour and surveillance program. In October 2008 he underwent a transurethral resection of the prostate (TURP). Histology of the prostatic chippings showed poorly differentiated TCC with prostatic invasion. A CT of his chest abdomen and pelvis revealed no lymph node involvement or metastatic spread. He therefore underwent a cystoprostato-urethrectomy with ileal conduit formation, in December 2008. In May 2010 the decision was made to perform a left inguinal orchidectomy as he presented with a craggy mass of his left testis, and there were clinical concerns that this was a tumour. Histology revealed that the left testis had been wholly replaced by a tumour. Taking into account his previous urological history, the features of this tumour are consistent with metastatic TCC, which is very rare.